Diversity mechanisms of long-term changes in phytoplankton biomass and productivity in the Southern Ocean: comparison in the Amundsen and Cosmonaut Seas - Zheng, Xinyu; Bai, Yan; Zhang, Yifan; He, Xianqiang; Li, Teng; Gong, Fang (Frontiers in Marine Science, 2025)
IntroductionGlobal warming and glacier melt are transforming Southern Ocean ecosystems, profoundly affecting phytoplankton dynamics. This study investigates long-term phytoplankton changes in the Amundsen and Cosmonaut Seas, focusing on responses to climate-driven environmental shifts and the influence of the Southern Annular Mode (SAM).MethodsWe analyzed high-resolution (4 km, monthly averaged) satellite-derived chlorophyll-a (Chla) and net primary productivity (NPP) data from austral summers (2003–2020). Environmental parameters, including sea surface temperature (SST), photosynthetically active radiation (PAR) and wind speed (WS), sea ice concentration (SIC) and mixed layer depth (MLD), were examined to elucidate their roles in driving phytoplankton variability in the Amundsen and Cosmonaut Seas.ResultsDuring positive SAM phases, Chla and NPP generally increased across both seas, but local ocean circulation led to divergent subregional trends. North of the Southern Antarctic Circumpolar Front (sACCF) and within the Weddell Gyre, enhanced wind-driven MLD promoted Chla increases. In the northern Ross Gyre, cooling SST and deeper MLD intensified upwelling and nutrient, sustaining Chla growth, while shallower MLD and weaker upwelling in the eastern Ross Gyre reduced Chla. In coastal Amundsen Sea, warming SST facilitated sea ice melt, increasing Chla, whereas cooling SST in the Cosmonaut Sea and Prydz Bay increased SIC, reducing Chla.DiscussionThis high-resolution analysis highlights the complex interplay of physical and biological drivers in polar marine ecosystems, providing critical insights into climate change impacts on Southern Ocean phytoplankton dynamics and their regional variability.